Un éloge de Camaldoli pour Pierre le Goutteux La Heremi descriptio de Ludovicus Camaldulensis monacus - Caby, Cécile (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2021)
The main object of this book is a manuscript preserved in Rome but composed in Florence in the middle of the fifteenth century, which transmits a text that is nearly unknown and highly original for at least three reasons. Firstly, the subject matter: a description of the Camaldoli hermitage at a time when this place was highly appreciated. Secondly, the discursive genre: the description of a built landscape, influenced both by humanist ekphrasis and by the tradition of medieval figurative exegesis. Finally, the dedicatee of the work, who is no less than Peter son of Cosimo dei Medici. The book successively examines the medieval and modern tradition of this little work, the identity of its author and the milieu of its production and first reception, and finally the details - some of them completely new - of the description of the Camaldolese hermitage and their textual and figurative tradition. It concludes with a critical edition of the work and the glosses with which it was enhanced in modern times. It is therefore a contribution not only to the history of an important Tuscan monastic centre, but also to that of the cultural and political networks of Tuscany in the second half of the fifteenth century, as well as to the knowledge of the textual and iconographic genres of landscape and monumental description, and finally, in a certain way, of modern Tuscan scholarship.